CHILDREN LEARNING DEVELOPMENT MODEL EARLY AGE BASED ON LOCAL CULTURE IN TK MAWAR DESA GANDASARI TOLANGOHULA DISTRICT, GORONTALO DISTRICT - TITIN ASURA NOHO TAHIR; RUSLIN W. BADU; ABDUL RAHMAT (International Journal of Innovations in Engineering Research and Technology, 2021)
The results of this study concluded that 1) Early childhood learning in Mawar Kindergarten in general refers to service standards in organizing paud learning. Local culture-based learning planning compiled in Mawar Kindergarten in the form of Curriculum, Syllabus, Semester Program, Weekly Learning Implementation Plan and daily learning plan; 2). TK Mawar implements integrated learning with local culture; 3) The factual model of learning is prepared using the results of mapping local cultures that exist in the paud environment as a reference in formulating material that will be delivered to students; 4) Factual model of local culture-based learning in TK Mawar then delivered to stakeholders involved and collaborating with TK Mawar to obtain responses and suggestions for improvement, then revised and enriched in the form of a draft development model for easier application of early childhood learning at the institution another paud.